Debonding-on-demand reversible adhesives via heat or light with competitive adhesion strength to conventional epoxy adhesives - Samantha J. (Lindholm) Knight; John D. McCoy; Sanchari Chowdhury; Youngmin Lee (Polymer Testing)
Stimuli responsive debonding-on-demand (DoD) reversible adhesives are of great interest for the circular economy. However, the reversible adhesives developed so far often lack competitive adhesion strength in a bonding state. In this work, reversible epoxy adhesives based on Diels–Alder (DA) chemistry were developed and exhibited a competitive adhesion strength (e.g., 12–16 MPa of a lap shear strength) to commercial non-reversible epoxy adhesives. The reversible epoxy formulation showed superior thermal stability up to 110 °C, and transition to a debonding state in the order of 0.1 MPa at 140 °C, consequently, an on/off-type debonding behavior. The transition to a debonding state was attributed to crosslinking density control (e.g., decrease by 33 %–49 %) through the reversible DA chemistry and the proximity to the glass transition. Next, for debonding by light stimulus, photothermal refractory plasmonic titanium nitride (TiN) nanoparticles were incorporated in the reversible epoxy, which can generate the required heat for debonding upon exposure to visible light. Photothermal debonding allows for precise debonding at target areas and tunable adhesion strength by controlling the exposure area and light intensity. The DA adhesive formulations containing 0.5 wt% TiN nanoparticles presented a debonding state with zero adhesion under light exposure with intensity of 1670 mW/cm2 (inducing 140 °C). Even after three cycles of reattachment, the DA adhesive formulations retained 96 % of the pristine sample's adhesion strength measured at 110 °C. Therefore, the DA adhesives are attractive candidates as reversible DoD systems applicable in higher temperatures.